Urbanization and Productivity : Evidence from Turkish Provinces Over the Period 1980-2000 - Coulibaly, Souleymane; Deichmann, Uwe; Lall, Somik (World Bank, Washington, DC, 2012)
Since the early 1980s, Turkey has been going through a rapid urbanization process at a pace beyond the World average. This paper aims at assessing the impact of this rapid urbanization process on the country's sector productivity. The authors built a database combining two-digit manufacturing data and some geographical, infrastructural, and socio-economic data collected at the provincial level by the Turkish State Institute of Statistics. The paper develops a parsimonious econometric relation linking sector productivity to accessibility, localization, and urbanization economies, proxying variables in the tradition of the New Economic Geography literature. The estimation results suggest that both localization and urbanization economies, as well as market accessibility, are productivity-enhancing factors in Turkey, although the causation link between productivity and these agglomeration measures is not clearly established. The sector-by-sector estimation confirms this result, although the localization economies effect is negative for the non-oil mineral sector, and the urbanization economies effect is weak for natural-resource-based sectors such as the wood and metal industry. Although the data cover the period up to 2000 and thus ignore the financial crisis that hit Turkey in 2001, the current structural transformation of the country away from the agricultural sector gives room to use the insights of these results as a preliminary step to understand the new challenges faced by the Turkish manufacturing sector. The results provide a discussion base to revisit the policy agenda on the improvement of the accessibility to markets, the improvement of the business environment to ease the creation and development of new firms, and a well-managed urbanization process to tap in the economic potential of cities.